Studi Tematik Terhadap Surah An-Nisa’ Ayat 34 Tentang Makna Dharb dalam Al-Qur’an - Achyar Zein; Insanissa'adah, Mar'atul; as-sayuti, Fadilatun Nisa; astuti, Rahayu Fuji (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study aims to understand and analyze: Explanation of the meaning of dharb in the Qur'an and interpretation of mufassir on the meaning of dharb in surah an-Nisa': 34. The method used is qualitative with the type of library research and is descriptive thematic analysis supported by primary data and secondary. The results of the study show that: the Qur'an explains the meaning of dharb with different meanings, such as making, making, being overwritten, traveling, hitting, walking, fighting, and trying (work). The author found a similarity of opinion among the mufassirs in interpreting the word dharb in Surah an-Nisa’: 34, that is, they only interpret the word dharb in the letter and verse which is meant to mean 'to hit', even though with different techniques and models. According to the author, if you look at the compilation and description of the meaning of the word dharb, you can be sure that the word does not only mean hitting as described by the commentators. On this basis, the author does not blame the interpretation of the mufassirs, but interpreting the word dharb in the verse to mean hitting alone is too narrow.